Education of clinical reasoning in patients with multimorbidity: a scoping review and perspectives for technology-enhanced learning - Consorti, Fabrizio; Borcea, Maria Carola; Laca, Angelo; Melcarne, Rossella; Scorziello, Chiara; Ventrone, Luca; Giacomelli, Laura (Frontiers in Education, 2023)
1 Multimorbidity is more and more frequent and defined as the co-existence of two or more chronic diseases in a patient. This condition poses new problems for clinical reasoning. Few studies inquired the construct of reasoning in multimorbidity and the teaching/learning methods. The objectives of this scoping review were searching for a definition of the construct of clinical reasoning in multimorbidity and the related learning methods, and special ways in which information technology can help. We searched PubMed, Scopus, ERIC and CORE databases. After an iterative process of selection and thematic analysis, we selected thirty articles, that were thematized in three classes: the multimorbid patient as a teacher (8 articles), defining a framework of competence (11 articles), representing multimorbidity and related clinical reasoning (11 articles). In this last theme were also grouped studies using technology to enhance learning. The construct of clinical reasoning in multimorbidity expands over three domains: clinical (the ability of managing uncertainty, anticipating, and detecting evolutions and conflicting guidelines, and setting priorities); relational (the ability of communicating uncertainty and developing a feasible, shared plan of care with the patient; organizational (the ability of managing the wide system of resources needed to take care of a multimorbid patient). The preferred teaching methods are the encounter with real or expert patients, technology enhanced case-based learning and graphical representations of clinical cases. Perspectives of research should be addressed to the development of rich, technology-enhanced simulations in which the learner can experience a patient's life-long time-lapse, move forth and back over time, explore the interactions among diseases and social determinants, among the possibly conflicting treatments.